PENGARUH KOMPETENSI DAN PELATIHAN KERJA TERHADAP KINERJA TENAGA PENDAMPING DESA KAB. SERDANG BEDAGAI DENGAN MOTIVASI SEBAGAI VARIABEL INTERVENING - Muhammad Taufik Lesmana; Mutiara Fadilah Amriani; Asrizal Efendy Nasution (Jurnal AKMAMI (Akuntansi Manajemen Ekonomi), 2026)
This study aims to determine and analyze the influence of competence and job training on the performance of Village Facilitators, as well as to test the role of motivation as an intervening variable. This study uses a quantitative method with the Partial Least Square (PLS) approach and involves 52 respondents who are village facilitators in Serdang Bedagai Regency. Data collection techniques through interviews and questionnaires. The results of the study indicate that competence has a significant effect on performance, job training has a significant effect on performance, competence does not have a significant effect on motivation, job training has a significant effect on motivation, motivation has a significant effect on performance, competence does not have a significant effect on the performance of village facilitators in Serdang Bedagai Regency through motivation as an intervening variable, and job training does not have a significant effect on the performance of village facilitators in Serdang Bedagai Regency through motivation as an intervening variable. .